ANALISIS CETAKAN PLASTIK INJEKSI SPESIMEN UJI TARIK MELALUI SIMULASI PLASTIK INJEKSI MENGGUNAKAN AUTODESK FUSION 360 - Supandi; Adhes Gamayel; Kasum; Sidik Mulyono; Mohamad Zaenudin (Scientific Journal of Mechanical Engineering Kinematika, 2024)
Plastic injection (injection molding) is a method of forming products from plastic pellets into various daily necessities products. In terms of supporting daily needs, plastic injection molded products must meet criteria, such as strength, ductility, flexibility, hardness, etc. One of the easiest ways is to do a tensile test. In this research, mold with the shape of tensile test specimen products was carried out through several process stages, namely design and simulation, fabrication, and product testing. Autodesk Fusion 360 software is used in the design process to simulate and predict material flow during the injection process into the mold with several parameter variations in the form of time, material temperature and mold temperature. The results obtained were by using polypropylene (PP) plastic material, the maximum injection conditions were by suing a melting temperature of 230Â°C and a mold temperature of 50Â°C with an injection time of 14.5 seconds, where it was predicted that the product would be easy to fill and the resulting quality would reach 100% good. This research has succeeded in designing and predicting a plastic injection process that can be utilized in the plastic molding process through the actual injection process in industries that use polypropylene material.